2008
DOI: 10.2119/2008-00077.bottai
|View full text |Cite
|
Sign up to set email alerts
|

Viability-Dependent Promoting Action of Adult Neural Precursors in Spinal Cord Injury

Abstract: The aim of the study was the assessment of the effects of adult neural stem cell (NSC) transplantation in a mouse model of spinal cord injury (SCI). The contusion injury was performed by means of the Infinite Horizon Device to allow the generation of reproducible traumatic lesion to the cord. We administered green fluorescent-labeled (GFP-)NSCs either by intravenous (i.v.) injection or by direct transplantation into the spinal cord (intraspinal route). We report that NSCs significantly improved recovery of hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 42 publications
3
49
0
Order By: Relevance
“…In experimental studies, cell therapeutics have been one of the approaches at the forefront of strategies aimed at promoting SCI repair. The introduction of a diversity of cell types, including Schwann cells (SCs) (Bamber et al, ; Barakat et al, ; Ghosh et al, ; Guest, Rao, Olson, Bunge, & Bunge, ; Paino and Bunge, ; Pearse et al, ; Schaal et al, ; Takami et al, ; Xu, Chen, Guenard, Kleitman, & Bunge, ; Xu, Guenard, Kleitman, Aebischer, & Bunge, ; Xu, Guenard, Kleitman, & Bunge, ; Xu, Zhang, Li, Aebischer, & Bunge, ), neural stem cells (NSCs) (Bottai, Madaschi, Di Giulio, & Gorio ; Cao et al, ; Karimi‐Abdolrezaee, Eftekharpour, Wang, Morshead, & Fehlings, ; Ogawa et al, ; Parr et al, ; Ziv, Avidan, Pluchino, Martino, & Schwartz, ), olfactory ensheathing cells (OECs) (Cao et al, ; Kubasak et al, ; Munoz‐Quiles, Santos‐Benito, Llamusi, & Ramon‐Cueto, ; Ramon‐Cueto, Cordero, Santos‐Benito, & Avila, ), mesenchymal stem cells (MSCs) (Cizkova, Rosocha, Vanicky, Jergova, & Cizek ; Kim, Oh, Lee, & Yoon ; Parr, Tator, & Keating, ), and bone marrow stromal cells (BMSCs) (Chiba et al, ; Fan, Du, Cheng, Peng, & Liu ; Neuhuber, Timothy Himes, Shumsky, Gallo, & Fischer, ; Ohta et al, ; Parr et al, ; Zurita and Vaquero, ), among others, have been reported independently to provide varying levels of improvement in tissue preservation, axon growth support, remyelination repair and axon conduction as well as functional recovery in animal models. However, unwanted side effects including the development of neuropathic pain (Hofstetter et al, ; Lang et al, ; Macias et al, ), and tumorgenicity (Lee, Tang, Rao, Weissman, & Wu, ) have been reported with cell transplants in some experimental paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies, cell therapeutics have been one of the approaches at the forefront of strategies aimed at promoting SCI repair. The introduction of a diversity of cell types, including Schwann cells (SCs) (Bamber et al, ; Barakat et al, ; Ghosh et al, ; Guest, Rao, Olson, Bunge, & Bunge, ; Paino and Bunge, ; Pearse et al, ; Schaal et al, ; Takami et al, ; Xu, Chen, Guenard, Kleitman, & Bunge, ; Xu, Guenard, Kleitman, Aebischer, & Bunge, ; Xu, Guenard, Kleitman, & Bunge, ; Xu, Zhang, Li, Aebischer, & Bunge, ), neural stem cells (NSCs) (Bottai, Madaschi, Di Giulio, & Gorio ; Cao et al, ; Karimi‐Abdolrezaee, Eftekharpour, Wang, Morshead, & Fehlings, ; Ogawa et al, ; Parr et al, ; Ziv, Avidan, Pluchino, Martino, & Schwartz, ), olfactory ensheathing cells (OECs) (Cao et al, ; Kubasak et al, ; Munoz‐Quiles, Santos‐Benito, Llamusi, & Ramon‐Cueto, ; Ramon‐Cueto, Cordero, Santos‐Benito, & Avila, ), mesenchymal stem cells (MSCs) (Cizkova, Rosocha, Vanicky, Jergova, & Cizek ; Kim, Oh, Lee, & Yoon ; Parr, Tator, & Keating, ), and bone marrow stromal cells (BMSCs) (Chiba et al, ; Fan, Du, Cheng, Peng, & Liu ; Neuhuber, Timothy Himes, Shumsky, Gallo, & Fischer, ; Ohta et al, ; Parr et al, ; Zurita and Vaquero, ), among others, have been reported independently to provide varying levels of improvement in tissue preservation, axon growth support, remyelination repair and axon conduction as well as functional recovery in animal models. However, unwanted side effects including the development of neuropathic pain (Hofstetter et al, ; Lang et al, ; Macias et al, ), and tumorgenicity (Lee, Tang, Rao, Weissman, & Wu, ) have been reported with cell transplants in some experimental paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, to the best of my knowledge, every publication that reported successful cell homing and performed behavioral and motor test reported significant positive outcomes-decreased tissue damage and/or improved health condition scores compared to untreated animals. Among numerous diseases studied, the most prominent examples include stroke, 3 spinal cord injury, 4 and amyotrophic lateral sclerosis. 2 Notably, although the IV approach yields rather low rates of cell homing (0.0005-10% of injected cells found in the CNS), cells that migrated to the brain acquired identical phenotypes regardless of administration route.…”
mentioning
confidence: 99%
“…Only at the end of the last century were NSCs found to be present in mammals (Reynolds and Weiss ; Bottai et al . , ; Givogri et al . ; Adami et al .…”
Section: Neural Stem Cells Descriptionmentioning
confidence: 99%
“…From then on, new possibilities of therapeutic approaches were imagined using these cells, hypothesizing their use in different neurological pathologies such as spinal cord injury, spinal muscular atrophy, amyotrophic lateral sclerosis, and Parkinson's disease (Bottai et al . , ; Pluchino et al . ; Corti et al .…”
Section: Neural Stem Cells Descriptionmentioning
confidence: 99%
See 1 more Smart Citation